PsycEXTRA Dataset 2006
DOI: 10.1037/e521242006-001
|View full text |Cite
|
Sign up to set email alerts
|

Mold Prevention Strategies and Possible Health Effects in the Aftermath of Hurricanes and Major Floods

Abstract: Extensive water damage after major hurricanes and floods increases the likelihood of mold contamination in buildings. This report provides information on how to limit exposure to mold and how to identify and prevent mold-related health effects. Where uncertainties in scientific knowledge exist, practical applications designed to be protective of a person's health are presented. Evidence is included about assessing exposure, clean-up and prevention, personal protective equipment, health effects, and public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 30 publications
(34 reference statements)
0
55
0
Order By: Relevance
“…One of the principal arguments against the hypothesis that S. chartarum causes adverse health effects in people is that the concentrations of Stachybotrys reported to cause toxicity in animal studies may not be achieved in water-damaged indoor air environments (Chapman et al 2003;Hossain et al 2004;Lai 2006). The total dose of SG used in the present study (20 mg) would represent exposure to a large number of Stachybotrys spores (2 Â 10 7 ) (Pestka et al 2008), which may only be encountered in heavily contaminated areas (Brandt et al 2006). However, SG is not only found in fungal spores, but is also present in viable and nonviable fungi and fungal fragments (Brasel et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the principal arguments against the hypothesis that S. chartarum causes adverse health effects in people is that the concentrations of Stachybotrys reported to cause toxicity in animal studies may not be achieved in water-damaged indoor air environments (Chapman et al 2003;Hossain et al 2004;Lai 2006). The total dose of SG used in the present study (20 mg) would represent exposure to a large number of Stachybotrys spores (2 Â 10 7 ) (Pestka et al 2008), which may only be encountered in heavily contaminated areas (Brandt et al 2006). However, SG is not only found in fungal spores, but is also present in viable and nonviable fungi and fungal fragments (Brasel et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Satratoxin-equivalent concentrations ranging from 2 to 330 ng/m 3 have been estimated to occur in rooms of water-damaged homes heavily contaminated with S. chartarum (Vesper et al 2000;Yike et al 1999). Acute, shortterm exposure to high airborne concentrations of SG is likely to occur in heavily contaminated environments, or during processes that disrupt nutrient sources for mold, such as would occur during mold remediation procedures (Brandt et al 2006). However, adverse health effects have also been associated with sustained or repeated exposure to damp indoor environments that are contaminated with S. chartarum, as would be expected in the workplace, home, or school (Park and Cox-Ganser 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Skin conditions related to this are particularly common, regardless of the type of mould or the extent of contamination [14] . In one study conducted in Thailand, it was found that eczema is the most common dermatosis during floods [15] .…”
Section: Skin and Eye Infectionsmentioning
confidence: 99%
“…According to estimates, over 1 600 people lost their lives in the resulting floods, with 14 million people across the region adversely affected [2,3] . Despite extensive relief and rescue operations, the death toll is expected to rise as thousands of people are still cut off from the rest of the country.…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 There has been increased interest in the use of new technologies for the remediation of mold and bacteria, especially since the prolonged flooding after Hurricanes Katrina and Rita in the New Orleans area resulted in highly contaminated buildings. [7][8][9] Among several techniques, the generation of gaseous chlorine dioxide (ClO 2 ) is currently being explored for the remediation of structures that have been impacted by microbial growth. The advantage of using a gas is that it can penetrate into building cavities.…”
Section: Introductionmentioning
confidence: 99%